Jacob Wonderbar for President of the Universe - Bransford, Nathan (Dial Books for Young Readers, 2012)
When seventh-grader Jacob Wonderbar is nominated for President of the Universe, he and his best friends Sarah Daisy and Dexter take off for outer space to campaign, and in the process suffer kidnappings, space monkeys, dirty politics, and threats to blow up the Earth.